A multidimensional approach to overcoming challenges in leading community college math tutoring success. Issue 6 (2nd June 2016) - Jaafar, Reem; Toce, Andi; Polnariev, Bernard A.
ABSTRACT: The United States lags behind many countries in mathematics proficiency. Quite often, students after graduating from high school are not prepared to enter college and are required to take remedial courses before taking credit-bearing math courses. This is particularly true at two-year institutions such as LaGuardia Community College, which provides the opportunity for students from a diverse background to attend college and earn a degree. Our college has created numerous initiatives to support the least prepared students. Our Mathematics Learning Center offers support for courses ranging from remedial mathematics through calculus and differential equations. In recent semesters, the mathematics department decided to dedicate a select group of faculty members to identify new ways of improving services at the center. In this paper, we argue for the need to give faculty a central role in assessing and devising appropriate policies for running a tutoring center. We discuss several challenges and solutions that would provide a multidimensional approach to students' educational experience at a public two-year urban college.